The effect of school smoke-free policies on smoking stigmatization: A European comparison study among adolescents - Robert, Pierre-Olivier (PLoS One, 2020)
The increasing denormalization of smoking by tobacco control policies and a normative smoke-free climate may shift power towards adolescent non-smokers. It is unclear, however, how common stigmatization of smokers is among adolescents or how stigmatization relates to the denormalization of smoking in their school and social environment. This paper aims to measure (1) whether stigmatization among European adolescents varies according to smoking status and socioeconomic position (SES), and (2) whether stigmatization is greater in school environments in which smoking is denormalized (i.e. those with low smoking rates and strong school tobacco policies). Data on 12,991 adolescents were collected in 55 schools in seven European countries (SILNE R-survey, 2016/17). We applied Stuber’s adapted scale of perceived stereotyping and discrimination towards smokers to smoking status and five variables indicating a power shift towards non-smokers: the school’s tobacco control policy (STP) score, the percentage of adolescents in the school who smoke, parents’ level of education, students’ academic performance, and the percentage of their friends who smoke. Multilevel regressions were applied to the global score for perceived stigmatization. Discrimination against smokers and stereotyping of smokers were frequently reported. Smokers reported less ‘perceived stigmatization of smoking’ than non-smokers (Beta = -0.146, p < 0.001). High-SES students reported stereotyping and discrimination more frequently than lower-SES students. The perception of stigmatization was lower among students whose academic performance was poor (Beta = -0.070, p < 0.001) and among those who had friends who smoked (Beta = -0.141, p < 0.001). Stigmatization was lower in schools with greater exposure to smoking and was not associated with the school’s STP score. Perceived stigmatization of smoking is common among European adolescents. Smokers themselves, however, perceive stigmatization less often than non-smokers. Strong school tobacco policies do not increase stigmatization, but a social environment that is permissive of smoking decreases perceived stigmatization.